The Expression of Slow-Growing Meromorphic Functions Sharing One Value CM with Their Derivatives (Communications in Mathematical Research, 2019)
In this paper, we study the relations between meromorphic functionsand their derivatives with one shared values, and obtain a concrete expression ofmeromorphic functions of zero order that share one value CM with their derivativesby a new method. Our main result is the supplementary of a related result due to Liand Yi (Li X M, Yi H X. Uniqueness of meromorphic functions sharing a meromorphicfunction of a small order with their derivatives. Ann. Polon. Math., 2010, 98(3):201–219).